Disparities in individual health behaviors between medicaid expanding and non-expanding states in the U.S. - Danielle Christine Rhubart (Elsevier, 2018)
Following the roll out of the Affordable Care Act, a significant amount of research has focused on health insurance coverage disadvantages experienced by those in states that chose not to expand Medicaid. This line of research has been used as a way to conceptualize potential disparities in future population health outcomes between states that did and did not expand Medicaid. While health insurance is certainly associated with health outcomes, health behaviors are equally, if not more, important. Therefore, to understand potential future population health outcomes - or lack thereof - this paper examines whether adults in states that did not expand Medicaid are also more likely to engage in health damaging behaviors (i.e. smoking, heavy drinking, physical inactivity, and overweight and obesity) than adults in states that expanded Medicaid. I find that those in states that did not expand Medicaid are more likely to be overweight and obese but are less likely to drink heavily compared to adults in states that did expand Medicaid. In part, higher rates of demographic and socioeconomic disadvantage explain higher rates of health damaging behaviors in states that did not expand Medicaid. This paper raises concerns about added long term consequences for population health and growing health disparities between states that did and did not expand Medicaid. Policy and practice implications of these findings are discussed. Keywords: Health behaviors, Medicaid expansion, Smoking, Obesity, Physical activity, Heavy drinking